Application of Internet of Things Energy System in Dynamic Risk Assessment of Composite Fault of Transmission Line. (5th May 2022) - Liu, Jie; Jia, Boyan; Ding, Likun; Zhang, Zhimeng; Sun, Cuiying
Abstract : In order to study the application of Internet of things energy system in complex fault risk dynamic assessment of transmission line. Firstly, the concept of power grid dynamic risk assessment is introduced, and the process of power grid dynamic risk assessment system based on Internet of things is designed. Then, it puts forward how to use the ubiquitous Internet of things multisource data to solve the key problems such as dynamic perception of fault probability, dynamic selection of fault set, dynamic generation of post fault state, and dynamic risk assessment of operation process. Finally, taking the maximum operation mode of a provincial power grid in summer 2013 as an example, this paper selects key 500 kV transmission lines for risk assessment, and the actual power grid example shows that. The power grid comprehensive risk assessment system considering the fault characteristics of transmission lines can effectively predict the fault probability of transmission lines; distinguish the two risks of high loss, low probability, and low loss and high probability; and provide guidance for operators. It is practical and effective.